Whole Genome Sequencing for Studying Helicobacter pylori Antimicrobial Resistance - Belén Fernández-Caso; Ana Miqueleiz; Teresa Alarcón (MDPI AG, 2023)
Antibiotic resistance (AMR) is an alarming concern worldwide and Helicobacter pylori, one of the most prevalent bacteria, is not an exception. With antibiotics being its primary therapy, increasing resistance leads to a higher rate of treatment failure. Understanding the genomic mechanisms of resistance to clarithromycin, levofloxacin, metronidazole, amoxicillin, tetracycline, and rifampicin through next-generation sequencing-based molecular tools, such as whole genome sequencing (WGS), can be of great value, not only to direct a patient's treatment, but also to establish and optimize treatment guidelines according to the local epidemiology and to avoid the use of inappropriate antibiotics. WGS approaches allow us to gain insight into the genomic determinants involved in AMR. To this end, different pipelines and platforms are continuously being developed. In this study, we take a more detailed view of the use and progression of WGS for in-depth study of H. pylori's AMR.